Engineered mesenchymal cell-based patches as controlled VEGF delivery systems to induce extrinsic angiogenesis. (15th September 2016) - Boccardo, Stefano; Gaudiello, Emanuele; Melly, Ludovic; Cerino, Giulia; Ricci, Davide; Martin, Ivan; Eckstein, Friedrich; Banfi, Andrea; Marsano, Anna
Graphical abstract: Abstract: Therapeutic over-expression of Vascular Endothelial Growth Factor (VEGF) by transduced progenitors is a promising strategy to efficiently induce angiogenesis in ischemic tissues (e.g. limb muscle and myocardium), but tight control over the micro-environmental distribution of the dose is required to avoid induction of angioma-like tumors. Therapeutic VEGF release was achieved by purified transduced adipose mesenchymal stromal cells (ASC) that homogeneously produce specific VEGF levels, inducing only normal angiogenesis after injection in non-ischemic tissues. However, the therapeutic potential of this approach mostly in the cardiac field is limited by the poor cell survival and the restricted area of effect confined to the cell-injection site. The implantation of cells previously organized in vitro in 3D engineered tissues could overcome these issues. Here we hypothesized that collagen sponge-based construct (patch), generated by ASC expressing controlled VEGF levels, can function as delivery device to induce angiogenesis in surrounding areas (extrinsic vascularization). A 7-mm-thick acellular collagen scaffold (empty), sutured beneath the patch, provided a controlled and reproducible model to clearly investigate the ongoing angiogenesis in subcutaneous mice pockets. VEGF-expressing ASC significantly increased the capillary in-growth inside both the patch itself and the empty scaffold compared to naïve cells, leading to significantly improved survival of implanted cells. These data suggest that this strategy confers control (i) on angiogenesis efficacy and safety by means of ASC expressing therapeutic VEGF levels and (ii) over the treated area through the specific localization in an engineered collagen sponge-based patch. Statement of Significance: Development of efficient pro-angiogenic therapies to restore the micro-vascularization in ischemic tissues is still an open issue. Although extensively investigated, the promising approach based on injections of progenitors transduced to over-express Vascular Endothelial Growth Factor (VEGF) has still several limitations: (i) need of a tight control over the microenvironmental VEGF dose to avoid angioma-like tumor growth; (ii) poor implanted cell survival; (iii) effect area restricted mainly to the injection sites. Here, we aimed to overcome these drawbacks by generating a novel cell-based controlled VEGF delivery device. In particular, transduced mesenchymal cells, purified to release a sustained, safe and efficient VEGF dose, were organized in three-dimensional engineered tissues to improve cell survival and provide a uniform vascularization throughout both the mm-thick implanted constructs themselves and the surrounding area.